Single nucleotide polymorphisms of the genes IL-2, IL-2RB, and JAK3 in patients with cutaneous leishmaniasis caused by Leishmania (V.) guyanensis in Manaus, Amazonas, Brazil - de Araújo Santos, Felipe Jules; da Silva, Lener Santos; Júnior, José do Espírito Santo; Ramos de Mesquita, Tirza Gabrielle; de Souza, Mara Lúcia Gomes; de Andrade Júnior, Moacir Couto; Talhari, Sinésio; Ramasawmy, Rajendranath (PloS one, 2019)
Leishmaniasis is a disease caused by intracellular protozoan parasites of the genus Leishmania. In endemic areas, only a portion of exposed subjects develops cutaneous leishmaniasis (CL), suggesting that the genetic inheritance of the host plays a vital role in both resistance and susceptibility to the disease. Interleukin-2 (IL-2) is a cytokine that plays a central role in the regulation of the immune response in infection through the axis IL-2/IL-2R (receptor) complex, triggering a series of intracellular events, among which the signaling of Janus kinase/signal transducers and activators of transcription (JAK-STAT). The present study aimed at verifying the possible relationship between single nucleotide polymorphism (s) (SNP s) in the genes IL-2, IL-2RB, and JAK3 in subjects with CL caused by Leishmania guyanensis in the city of Manaus, state of Amazonas, Brazil. 820 patients with CL and 850 healthy subjects (control group) coming from the same endemic areas as the patients were examined. The SNPs -2425G/A (rs4833248) and -330 T/G (rs2069762), located in the IL-2 gene promoter region, seem to influence the expression of the gene and the SNP +10558G/A (rs1003694) and +13295T/C (rs3212760) located in the 3rd intron of the IL-2RB gene and the 13th intron of the JAK3 gene, respectively, were studied by PCR-RFLP. Genotypes and alleles frequencies were obtained by direct counting. For the comparison between the two groups, the χ2 test with OR (odds ratio) and the 95% confidence interval (CI) were used. Similar genotypes and alleles frequencies for the different SNPs were observed in both patients with CL and healthy controls. Comparison of genotypic and allelic frequency between patients with CL and healthy subjects did not show any difference. These polymorphisms do not predict susceptibility to, or protection against the development of CL caused by L. guyanensis in the Amazonas.